Surviving disaster (British Broadcasting Corporation, 2009)
This gripping series brings to life the dramatic stories of those involved in some of the greatest catastrophes of our time. Revealing the truth behind seven iconic disasters, each episode considers whether the disaster could have prevented, and look at the lessons to be learnt in order to avoid future large-scale catastrophers